Safe sanitation: Findings from the impact evaluation baseline survey in Thiruvarur, Tamil Nadu, India ; Financial Inclusion Improves Sanitation and Health - FINISH Project - Britta Augsburg (Institute for Fiscal Studies (IFS), 2011)
FINISH - Financial Inclusion Improves Sanitation and Health - is a joint undertaking of a wide range of actors that came together to address the challenges of micro finance, insurance and sanitation and health. The overall goal of the project itself is to built 1 million safe toilets (possibly sanitation systems), financed through microfinance loans.
Keywords: 330